The Politics of Musical Time : Expanding Songs and Shrinking Markets in Bengali Devotional Performance - Graves, Eben (Book collections on Project MUSE., 2022)
"How does sacred music contribute to modern social life in South Asia? Due to time constraints in commercial contexts, Bengali musicians have had to adopt techniques of popular music to promote their own religious musical careers and religious perspectives. The Politics of Musical Time traces a lineage of the devotional song known as kīrtan in the Bengal region of India over the past century to demonstrate the shifting meanings of devotional performance. Focusing on padābalīkīrtan, a long format that combines devotional song and storytelling, Eben Graves examines how expressions of religious affect and political belonging are strained in contemporary, shortened performance time frames. To illustrate the political economy of performance in South Asia, Graves also explores how religious performances and texts interact with issues of nationalism, gender, and economic exchange. Combining ethnography, history, performance analysis, and videos from the author's fieldwork in India, The Politics of Musical Time reveals how, over centuries, devotional performances in East India have used musical time to express ideas about the sacred and the modern"--